Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Financial Technology Terhadap Minat Investasi Generasi Z Kabupaten Sidoarjo - Okvily, Ihcya; Takarini, Nurjanti (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Investment is crucial not only for ensuring financial independence in the future but also for protecting asset value against inflation. However, public interest in investment in Indonesia remains low, despite its potential to support the growth and stability of the capital market. This study aims to identify factors influencing investment interest, focusing on the roles of financial technology, financial inclusion, and financial literacy. The study's population consists of Generation Z members residing in Sidoarjo, with a sample of 100 respondents selected purposively using the Slovin formula. Primary data was collected through surveys, and analysis was conducted using SmartPLS. The results show that financial technology, financial inclusion, and financial literacy have a positive impact on investment interest. These findings suggest that increasing access to financial services, such as Investment Galleries and stock account openings, can enhance Generation Z’s interest in investing. Therefore, improving access and financial education could be key in encouraging more people, especially the younger generation, to participate in the capital market. The implications of this study highlight the need for policymakers and financial institutions to design targeted programs that strengthen financial awareness and accessibility for young investors.